Case reportsOne step behind to step ahead – femoral approach to stabilize and to extract functional pacing lead to regain venous access - Maciąg, Aleksander; Syska, Paweł; Kuśmierski, Krzysztof; Broy, Beata; Sterliński, Maciej (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Transvenous lead extraction can be a method to regain venous access. We present the case of a man, aged 67, with indications to upgrade an ICD to a resynchronization therapy device. Since innominate vein occlusion was diagnosed and extraction of an abandoned ventricular pacing lead did not provide lumen regain, a functional atrial lead was extracted with the femoral approach to stabilization and venous access was regained. Asymptomatic vein wall damage but no other complications were recorded. The simultaneous application of different techniques to regain venous access may allow success of the final procedure in system upgrading.